Reversed Solutionism. The Two Sided Control of Crowdwork - Heiland, Heiner (PARTECIPAZIONE E CONFLITTO, 2019)
Platform labour is a new phenomenon that brings new forms of labour control with it. The article looks at crowdwork and analyses the various types of control inherent in this phenomenon. It is argued that crowdwork is not controlled by technological instruments alone, such as algorithms. Indeed, the method of organising labour is a complementary control element. Analytically, a technological and an organisational fix can be distinguished. Their specific characteristics are empirically investigated on the basis of crowdwork platforms covering the entire spectrum of qualifications. The result is that already existing asymmetries between capital and labour are intensified by the interaction between the technological and the organisational fix.